Plasmid-encoded toxin of Escherichia coli cleaves complement system proteins and inhibits complement-mediated lysis in vitro - Correa, Gabriel B.; Freire, Claudia A.; Dibo, Miriam; Huerta-Cantillo, Jazmin; Navarro-Garcia, Fernando; Barbosa, Angela S.; Elias, Waldir P.; Moraes, Claudia T. P. (Frontiers in Cellular and Infection Microbiology, 2024)
Plasmid-encoded toxin (Pet) is an autotransporter protein of the serine protease autotransporters of Enterobacteriaceae (SPATE) family, important in the pathogenicity of Escherichia coli. The pet gene was initially found in the enteroaggregative E. coli (EAEC) virulence plasmid, pAA2. Although this virulence factor was initially described in EAEC, an intestinal E. coli pathotype, pet may also be present in other pathotypes, including extraintestinal pathogenic strains (ExPEC). The complement system is an important defense mechanism of the immune system that can be activated by invading pathogens. Proteases produced by pathogenic bacteria, such as SPATEs, have proteolytic activity and can cleave components of the complement system, promoting bacterial resistance to human serum. Considering these factors, the proteolytic activity of Pet and its role in evading the complement system were investigated. Proteolytic assays were performed by incubating purified components of the complement system with Pet and Pet S260I (a catalytic site mutant) proteins. Pet, but not Pet S260I, could cleave C3, C5 and C9 components, and also inhibited the natural formation of C9 polymers. Furthermore, a dose-dependent inhibition of ZnCl2-induced C9 polymerization in vitro was observed. E. coli DH5α survived incubation with human serum pre-treated with Pet. Therefore, Pet can potentially interfere with the alternative and the terminal pathways of the complement system. In addition, by cleaving C9, Pet may inhibit membrane attack complex (MAC) formation on the bacterial outer membrane. Thus, our data are suggestive of a role of Pet in resistance of E. coli to human serum.